Strategi Pengembangan Agroindustri Kakao Berbasis Kelompok Tani Di Propinsi Sumatera Barat (Universitas Esa Unggul, 2012)
AbstractWest Sumatrasince 2005 was declaredas a center for Indonesian cocoaat western portion. Various programs for the production and productivity of cocoa launched by the provincial government and the central government. Neither the form ofthe expansion of planting area and also the provision of quality seeds of cocoa. Almost allareasin West Sumatra suitable for the cultivation of cocoa, so the cocoa planting area covers almost all the districts in the province. Added acreage make significant increase of cocoa production in West Sumatra. Increased production, planning should be made to anticipate the marketing of cocoa production people. One way is to establish agro-based cocoa in West Sumatra province. This paper will discuss the selection of the center location sand their cocoa agro-based development strategy community. The selectionis based on the development strategy of the group with the intention that added value can come enjoyed by the group. The plan consists ofa medium-term strategy and along term target of total area and total production.Keywords: cocoa, strategicplans, MPE, AHP